2011
DOI: 10.3928/01913913-20100618-05
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus in Pediatric Lens Disorders

Abstract: The authors believe it is imperative that great attention should be given to ocular alignment in addition to management of refractive error and intense amblyopia therapy during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…This is consistent with previous reports of similar patients (Spanou 76.5%, Parks and Hiles 66%, Cheng 59%, Lambert 50%), 1,3,5,13,14 In our study, esotropia occurred more frequently in the contact lens group. Vertical deviations were uncommon (1.9%) at 12 months postoperatively.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous reports of similar patients (Spanou 76.5%, Parks and Hiles 66%, Cheng 59%, Lambert 50%), 1,3,5,13,14 In our study, esotropia occurred more frequently in the contact lens group. Vertical deviations were uncommon (1.9%) at 12 months postoperatively.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of strabismus prior to surgery was 24.6% and by 12 months after surgery had risen to 70.4%, which conforms with previous reports of strabismus in the setting of monocular congenital cataracts. [1][2][3][4][5][6][7][8][9][10] Other studies have shown occurrence rates from 55% to 100%. 2,5 In IATS, the development of strabismus was not affected by the occurrence of an adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Prior reports have suggested that strabismus develops less frequently when an intraocular lens (IOL) is implanted primarily. 1,2 Such reports are limited by retrospective design and small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The prevalence of strabismus ranges from less than 0.5% to about 5% in different communities and countries. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, the prevalence is substantially higher in some diseases, such as Down or Marfan syndrome. 21,26 Available population-based studies on strabismus have mostly addressed binocular vision problems besides amblyopia and very few studies have exclusively evaluated strabismus.…”
Section: Introductionmentioning
confidence: 99%
“…21,26 Available population-based studies on strabismus have mostly addressed binocular vision problems besides amblyopia and very few studies have exclusively evaluated strabismus. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] One of the most important questions about strabismus is the ratio of esotropia to exotropia, which is different in different countries. Although most studies have reported that esotropia is more prevalent, most strabismic patients have exotropia in East Asian countries.…”
Section: Introductionmentioning
confidence: 99%